Is it necessary for clinical tumor volume including neck muscles in target volume delineation of nasopharyngeal carcinoma? - Fei Chen; Xiangquan Kong; Haixia Wu; Weining Fang; Zhaodong Fei; Zhupeng Wu; Dan Zhao; Liqin Ma (Laryngoscope Investigative Otolaryngology, 2021)
Abstract Objectives To calculate the shrinkage of the neck muscles and dosimetric changes and to clarify the necessity of covering part of the muscle in neck node region delineation for patients with nasopharyngeal carcinoma (NPC) treated with intensity‐modulated radiotherapy. Methods In total, 44 patients with NPC were enrolled. Distances between the lateral border of the neck muscles and longitudinal midline were measured on every selected slice. This process was repeated three times, and the mean values of the three distances of planning computed tomography (CT) images and repeated CT images were adopted (labeled d1 and d2). The mean value of the differences between d1 and d2 was regarded as the medial shrinkage of the neck muscles. The initial clinical target volume of cervical lymph nodes (CTV‐n) was shifted medially with the value of shrinkage, yielding a new CTV‐n. Doses that covered 95% of the planning tumor volume (PTV) (D95), 99% of the PTV (D99), mean dose (Dmean), and maximum dose (Dmax) were used to calculate the dosimetric variation between the initial and new CTV‐n. Comparisons were performed using the paired samples t test. Results The median d1 was 3.81 cm (range: 1.19‐8.20 cm), and the median d2 was 3.68 cm (range: 0.94‐9.59 cm), with a statistically significant difference (P < .001). The mean difference between d1 and d2 was 1.5 ± 3.1 mm (SD). The D95 and D99 of PTV of initial CTV‐n decreased by 0.38% and 0.62% (P < .001 and P < .001, respectively). Conclusion Patients with NPC experienced medial shrinkage of the neck muscles by 1.5 mm, and the consequent dose variation was negligible. It is unnecessary to cover part of the muscles in the delineation of the CTV‐n.